Archaeology and archaeometry : from casual dating to a meaningful relationship? - Killick, David
Most archaeology and anthropology departments are grouped as Humanities or as Social Sciences in university organizations. Where does that place the archaeometrists who approach the materials with the methods of physical and biological sciences? And where does it place the archaeologists themselves Ñ especially when archaeometric studies have a large place in contract archaeology?